2018
DOI: 10.3912/ojin.vol23no02ppt22
|View full text |Cite
|
Sign up to set email alerts
|

Moving Shift Report to the Bedside: An Evidence-Based Quality Improvement Project

Abstract: A Midwestern, 532-bed, acute care, tertiary, Magnet® designated teaching hospital identified concerns about fall rates and patient and nurse satisfaction scores. Research has shown that the implementation of bedside report has increased patient safety and patient and nurse satisfaction. An evidence-based practice change incorporating bedside report into standard nursing care was implemented and evaluated over a four-month time period on three nursing units. Fall rates, HCAHPS and Press Ganey® scores, and nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Some questioned the value of the process. Similar nurse sentiments are also echoed in the literature 3,4…”
Section: Identifying a Need For Changesupporting
confidence: 64%
See 1 more Smart Citation
“…Some questioned the value of the process. Similar nurse sentiments are also echoed in the literature 3,4…”
Section: Identifying a Need For Changesupporting
confidence: 64%
“…Similar nurse sentiments are also echoed in the literature. 3,4 Routine patient satisfaction surveys indicated a need to improve communication among caregivers. Specifically, patients and family members have commented that nurse communication about care plans seemed disconnected and that each shift was not communicating important events to the next.…”
Section: Identifying a Need For Changementioning
confidence: 99%
“…Bedside nurse involvement will be imperative to make nursing practice changes. In an evidence-based practice change conducted by McAllen et al, 8 BSR was put into practice of nursing care at 1 tertiary Magnet hospital. The nurse-driven implementation of BSR had an impact postimplementation to not only the patients' experience but also the bedside nurse's satisfaction and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…patients were either satisfied or their satisfaction increased relative to baseline after participating in a QI project. 21,24,30,34,39,41 However, Ayaad et al 36 found no difference in patient satisfaction scores.…”
Section: Outcomes Of Qi Projectsmentioning
confidence: 99%
“…Klee et al 40 applied a standardized handover communication tool to all units in the action stage of the PDSA method after examining the successful changes in surgical units during the investigation stage. However, the other 5 studies 24,26,[32][33][34] did not follow the key principles of the PDSA method and most of the QI projects were limited to small-scale studies.…”
Section: Description Of Studiesmentioning
confidence: 99%